Tinjauan Terhadap Pembinaan Anak Yatim: Perspektif Hukum Islam Dan Implementasinya Dalam UU Perlindungan Anak Di Panti Asuhan Al Madinah - Putri Andini; Sthepany Tobing; Tri Santa L. Mahulae; Syuratti A Rahayu Manalu (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2023)
Children as a generation of the nation come from various levels of society, rich, poor, and some are orphans or orphans. This condition also gives rise to social and anti-social behavior towards children. From this we can see that the role of guardians or institutions that act as guardians to realize Law No. 35 of 2014 is very important and one of them is an orphanage which serves as guardian for orphaned, neglected and underprivileged children. The aim of this research is to explore the pattern of fostering foster children at the Al Madinah Orphanage, from the perspective of Islamic law and the Child Protection Law. The research method we use is a qualitative descriptive method. The location of the research is the Al Madinah Orphanage. Researchers found that there were four coaching patterns used in the spiritual coaching pattern which is closely related to religion, the second is the moral coaching pattern which is related to the social life of foster children, the third is the mental coaching pattern and the fourth is the physical coaching pattern.